A biomechanical approach to investigate swing characteristics in elite golfers. Issue 7 (July 2019) - Fuyu, Mayaw; Lee, Hui-Min; Chen, Po-Yin; Chou, Li-Wei; Wei, Shun-Hwa
Abstract : Background: The current study aims to compare the variability of positional control of the club in the starting period of downswing and the orientation of the clubface during impact in elite and intermediate golfers. Methods: Seven elite and 13 intermediate golfers were recorded by an eight-camera VICON motion capture system while putting with a pitch club. Six retro-reflective markers were attached to the club to build a biomechanical model for analyzing swinging movements. Group comparisons of outcome variables regarding the turning point, sweet spot, elevation angle (EA), and azimuth angle (AA) of the club head were made between the elite and intermediate players. Results: There were significant differences between groups in SDs of the location of the club tail along the x, y, and z axes at the turning point (x, p = 0.004; y, p = 0.015; and z, p = 0.035); the minimum distance between the center of the sweet spot and the ball at impact ( p = 0.007); the EA ( p = 0.001); and the AA ( p = 0.001) of the club head. Results showed that the elite players displayed more converged locations of turning points, shorter distances between the center of the sweet spot and the ball at impact, greater EAs, and smaller AAs compared with those of the intermediate players. Conclusion: These findings proposed a biomechanical approach of a practical way to observe swing behaviors. These findings suggest that the stability of locations of turning points is a golden reference for differentiating levels of golfers' performance.